Investigation on the Composition of Agarose-Collagen I Blended Hydrogels as Matrices for the Growth of Spheroids from Breast Cancer Cell Lines - Alessandra Quarta; Nunzia Gallo; Daniele Vergara; Luca Salvatore; Concetta Nobile; Andrea Ragusa; Antonio Gaballo (MDPI AG, 2021)
Three-dimensional (3D) cell culture systems mimic the structural complexity of the tissue microenvironment and are gaining increasing importance as they resemble the extracellular matrix (ECM)-cell and cell-cell physical interactions occurring in vivo. Several scaffold-based culture systems have been already proposed as valuable tools for large-scale production of spheroids, but they often suffer of poor reproducibility or high costs of production. In this work, we present a reliable 3D culture system based on collagen I-blended agarose hydrogels and show how the variation in the agarose percentage affects the physical and mechanical properties of the resulting hydrogel. The influence of the different physical and mechanical properties of the blended hydrogels on the growth, size, morphology, and cell motility of the spheroids obtained by culturing three different breast cancer cell lines (MCF-7, MDA-MB-361, and MDA-MB-231) was also evaluated. As proof of concept, the cisplatin penetration and its cytotoxic effect on the tumor spheroids as function of the hydrogel stiffness were also investigated. Noteworthily, the possibility to recover the spheroids from the hydrogels for further processing and other biological studies has been considered. This feature, in addition to the ease of preparation, the lack of cross-linking chemistry and the high reproducibility, makes this hydrogel a reliable biomimetic matrix for the growth of 3D cell structures.